PENERAPAN PEMBELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN RECIPROCAL DALAM MENGATASI KESALAHAN SISWA MENYELESAIKAN SOAL MATEMATIKA KELAS IX SMP N 1 PAKUSARI POKOK BAHASAN STATISTIKA SEMESTER GANJIL TAHUN AJARAN 2012/2013 - Niken, N; Susanto, S; Setiawan, Toto’ Bara (KadikmA, 2012)
Abstract. Reciprocal teaching is a learning approach that implements four independent comprehension strategies namely summaries, preparing questions, clarify and then predict. It can also improve the students achievement in the classroom so it can minimalize studentâs error in the topic of statistics. The subject of the research is grade IXF students of SMPN 1 Pakusari. The data collection methods used in this research are test, interview, observation, and documentation.. The result showed that there are decreasing in every error; 9,38% and 3,57% for data used error; 16,96% and 0,89% for used theorem and definition error; 10,71% and 17,41% for technique error and 3,57% and 1,76% for other error. The result also showed that the teaching learning activity using reciprocal teaching got a good responses from the teacher and students, only a few of them had a poor responses. Those good responses were proved by the improvement of studends activity that use all of the body. Beside, there is also an effect on students thought between before and after teaching and learning process. Those all showed that reciprocal teaching can shift the students minimalize the students error in learning esspesially in the topic of statistics Key Words: Reciprocal Teaching, studentâs error, statistics